Strategic leadership and innovation at Apple Inc. - Heracleous, Loizos Th.; Papachroni, Angeliki (London : SAGE Publications Ltd, 2016)
The case describes the successful tenure of Steve Jobs as CEO of Apple and how he succeeded in creating one of the wealthiest and most innovative companies in the world. The student is invited to consider what will happen to the company after Steve Jobs' death under the leadership of Tim Cook and whether Apple can replicate its success of previous years.
Originally published in Heracleous, L., & Angeliki, P. (2016). Strategic leadership and innovation at Apple Inc. In S. Paroutis, L. Heracleous, & D. Angwin (Eds), Practicing strategy: Texts and cases (2nd ed., pp.168-190). London, UK: SAGE Publications Ltd. ISBN: 9781473912854.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; Jobs, Steve, -- 1955-2011.; Cook, Timothy D., -- 1960-; electronic books; Apple Computer, Inc. -- Technological innovations